Buried late Quaternary channel systems in the Danish North Sea – Genesis and geological evolution. (1st November 2019) - Prins, Lasse Tésik; Andresen, Katrine Juul
Abstract: The Danish North Sea has been subject to extensive seismic surveying (both 2D and 3D) during the past four decades. The 3D seismic data from the area has mainly been used for hydrocarbon exploration, but in the last decade, it has also been utilized for investigating the Quaternary sediments and especially buried incised valleys. The erosional and depositional processes involved in forming such valleys are important in paleolandscape reconstruction, but are often difficult to determine, since sediment deposited by flowing water, displays ambiguous geometric structures. In this study, we combine the analysis of infill geometries, from high-resolution 2D seismic data, with plan-view morphology analysis, from 3D seismic data, and lithological data from borehole reports, in order to constrain the origin of buried channels in the Danish North Sea. This data integration makes differentiations of a subaerial vs. subglacial origin more robust. The study focusses on analyzing a proglacial to fluvial channel system, which was initiated as a subglacial tunnel valley system during the Last Glacial Maximum, and subsequently evolved as a fluvial system after deglaciation. The channel system was active in a marsh environment during a period of subaerial exposure in the late Weichselian to early Holocene. During the Holocene transgression, the system was gradually flooded leaving estuarine tidal deposits in the underfilled channels. Once the area was completely flooded, the channel system was buried under marine sands. Highlights: Evidence for fluvial reoccupation of tunnel valleys upon deglaciation. Morphological evidence for the non-marine to brackish to marine transition during the Holocene in the North Sea. Morphological evidence for the Last Glacial Maximum ice extent in the Danish North Sea. Seismic time slice analysis and High-Res. 2D seismic facies analysis improves the interpretation of the shallow geology.